Fostering Environmental Awareness Through Poster Media: A Case Study at SD Inpres 3 Talise - Gustina M Yusup; Azizah Azizah; Khairunnisa Khairunnisa; Abdul Rahman; Sukri Sukri (Journal of Innovation and Research in Primary Education, 2026)
Environmental awareness among elementary students remains inadequate despite its critical importance for sustainable development. This qualitative case study investigated poster media implementation to foster environmental awareness at SD Inpres 3 Talise, examining implementation processes, behavioral changes, and obstacles encountered by educators. Twenty-four students from grades III, IV, and V, three homeroom teachers, and the school principal participated. Data were collected through systematic observations, semi-structured interviews, and documentary evidence, analyzed using the Miles and Huberman framework with triangulation for validity. Results revealed that strategically positioned posters combined with peer modeling effectively enhanced environmental awareness, with fifth-grade students demonstrating autonomous environmental behaviors, fourth-grade students showing consistent conduct requiring occasional reinforcement, and third-grade students displaying gradual improvements with substantial teacher guidance. Unexpected findings included spontaneous peer mentoring dynamics and location-dependent poster effectiveness. Seven implementation obstacles emerged: inconsistent student attention, attitude-behavior gaps, novelty effects, suboptimal placement, resource limitations, inadequate pedagogical integration, and limited teacher understanding of visual media pedagogy. Findings align with Mayer's Cognitive Theory of Multimedia Learning, Bandura's Social Learning Theory, and Ajzen's Theory of Planned Behavior, demonstrating that posters function optimally as pedagogically integrated tools requiring strategic placement, content refreshment, and instructional reinforcement rather than passive displays. This study contributes practical insights for implementing cost-effective visual media interventions in resource-constrained educational settings.